Lenalidomide plus dexamethasone versus observation in patients with high-risk smouldering multiple myeloma (QuiRedex): long-term follow-up of a randomised, controlled, phase 3 trial. Issue 8 (August 2016) - Mateos, María-Victoria; Hernández, Miguel-Teodoro; Giraldo, Pilar; de la Rubia, Javier; de Arriba, Felipe; Corral, Lucía López; Rosiñol, Laura; Paiva, Bruno; Palomera, Luis; Bargay, Joan; Oriol, Albert; Prosper, Felipe; et al.
Summary: Background: The standard of care for smouldering multiple myeloma is observation. We did the QuiRedex study to compare early treatment with lenalidomide plus dexamethasone with observation in patients with high-risk smouldering multiple myeloma. Here we report the long-term follow-up results of the trial. Methods: We did this open-label, randomised, controlled phase 3 study at 19 centres in Spain and three centres in Portugal. Patients aged 18 years or older with high-risk smouldering multiple myeloma were randomly assigned (1:1), via a computerised random number generator, to receive either early treatment with lenalidomide plus dexamethasone or observation, with dynamic balancing to maintain treatment balance within the two groups. Randomisation was stratified by time from diagnosis of smouldering multiple myeloma to study enrolment (≤6 months vs >6 months). Patients in the treatment group received nine 4-week induction cycles (lenalidomide 25 mg per day on days 1–21, plus dexamethasone 20 mg per day on days–1–4 and days 12–15), followed by maintenance therapy (lenalidomide 10 mg per day on days 1–21 of each 28-day cycle) up to 2 years. Group allocation was not masked from study investigators or patients. The primary endpoint was time from randomisation to progression to symptomatic myeloma. The primary analysis was based on the per-protocol population, restricted to patients who fulfilled the protocol in terms of eligibility. Safety assessments were based on the intention-to-treat population. This trial is registered withClinicalTrials.gov, numberNCT00480363 . Findings: Between Nov 8, 2007, and June 9, 2010, 125 patients were enrolled and underwent randomisation. 119 patients comprised the per-protocol population and were randomly assigned to receive either lenalidomide plus dexamethasone (n=57) or observation (n=62). The cutoff date for this update was June 30, 2015. Median follow-up for surviving patients was 75 months (IQR 67–85). Lenalidomide plus dexamethasone continued to provide a benefit on time to progression compared with observation (median time to progression not reached [95% CI 47 months–not reached] vs 23 months [16–31]; hazard ratio [HR] 0·24 [95% CI 0·14–0·41]; p<0·0001). Progression to multiple myeloma occurred in 53 (86%) of 62 patients in the observation group compared with 22 (39%) of 57 patients in the treatment group. At data cutoff, ten (18%) patients had died in the treatment group and 22 (36%) patients had died in the observation group; median overall survival from the time of study entry had not been reached in either group (95% CI 65 months–not reached vs 53 months–not reached; HR 0·43 [95% CI 0·21–0·92], p=0·024). Survival in patients who had received subsequent treatments at the time of progression to active disease did not differ between groups (HR 1·34 [95% CI 0·54–3·30]; p=0·50). The most frequently reported grade 3 adverse events in patients given lenalidomide plus dexamethasone were infection (four [6%]), asthenia (four [6%]), neutropenia (three [5%]), and skin rash (two [3%]); these events all occurred during induction therapy. No grade 4 adverse events occurred, but one (2%) patient in the lenalidomide plus dexamethasone group died from a respiratory infection during induction therapy The frequency of second primary malignancies was higher in patients in the treatment group than in those in the observation group (six [10%] of 62 patients vs one [2%] of 63 patients), but the cumulative risk of development did not differ significantly between the groups (p=0·070). Interpretation: This study is, to our knowledge, the first randomised trial in which early treatment has been assessed in selected patients with high-risk smouldering multiple myeloma. Positive results from ongoing trials would support the use of early treatment for patients with high-risk disease in the near future. Funding: Pethema (Spanish Program for the Treatment of Hematologic Diseases).